Evaluation of ‘Visual prostate symptom score’ in men with benign enlargement of prostate in a tertiary care center in midwestern Nepal - Gupta, Dipesh Kumar (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Quantification of lower urinary tract symptoms (LUTS) in patients with benign enlargement of prostate (BEP) is required to initiate and regulate treatment. Among many, International Prostate Symptom Score (IPSS) is standard though it is time consuming and difficult to understand by many patients. A recent Visual Prostate Symptom Score (VPSS) which is presumed to be simpler and well understood by patients with lower educational status has been in use. Methods: This is a prospective observational study conducted in Nepalgunj Medical College, Nepalgunj. In a total of 79 patients, 25 patients of LUTS because of other causes were excluded and 54 patients clinically diagnosed with BEP were enrolled for the study over a period of one year. Symptom evaluation was done in all with both IPSS and VPSS and uroflowmetry parameters were also recorded. The IPSS and VPSS were compared with each other and also with uroflowmetry parameters. Results: Mean age of the patients was 67 years and mean prostate volume was 48 gm. The patients who mostly were farmers had median eighth grade of education. Fourteen were illiterates and 40 were literate patients. Significant number of patients required assistance of a medical personnel to complete IPSS (p= <0.001) including those in literate group as well (p= <0.001). Time taken to complete VPSS was significantly less (p= 0.019). Total IPSS correlated with total VPSS ((r= +0.36; p=0.007). There was negative and significant correlation of VPSS with uroflowmeter parameters while IPSS failed to do so. Conclusion: VPSS is an easy and reliable tool to assess symptom severity in cases of BEP presenting with LUTS. It has the added advantage of utility in assessment of LUTS in patients with lower educational status. Moreover, the patients take shorter time to complete the questionnaire. Journal of Society of Surgeons of Nepal, 2015; 18 (2), page: 6-10